Nitric oxide induces specific isoforms of antioxidant enzymes in soybean leaves subjected to enhanced ultraviolet-B radiation - Santa Cruz, Diego Mario (2014)
Antioxidant enzymes play a key role in plant tolerance to different types of stress, including ultraviolet-B (UV-B) radiation. Here we report that nitric oxide (NO) enhances antioxidant enzymes gene expression and increases the activity of specific isoforms protecting against UV-B radiation. Pre-treatments with sodium nitroprussiate (SNP), a NO-donor, prevented lipid peroxidation, ion leakage and H2O2 and superoxide anion accumulation in leaves of UV-B-treated soybean plants. Transcripts levels of superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) were significantly induced by SNP. These data correlated with the enhancement of particular antioxidant enzyme isoforms, such as one CAT isoform and two APX isoforms. Moreover, SNP induced the expression of three new isoforms of SOD, identified as Mn-SOD subclass. Further results showed that total activities of SOD, CAT and APX significantly increased by 2.2-, 1.8- and 2.1-fold in SNP-treated plants compared to controls, respectively. The protective effect of SNP against UV-B radiation was negated by addition of the specific NO scavenger cPTIO, indicating that NO released by SNP mediates the enhancement of antioxidant enzymes activities. In conclusion, NO is involved in the signaling pathway that up-regulates specific isoforms of antioxidant enzymes protecting against UV-B-induced oxidative stress.